2022
DOI: 10.1111/jocd.15219
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three different surgical approaches for the treatment of large/giant congenital melanocytic nevus

Abstract: Objective Treating large/giant congenital melanocytic nevus (L/GCMN) is challenging for surgeons. Operative approaches commonly used to remove L/GCMN include serial excision, tissue expansion, and skin grafting. Thus, we retrospectively compared these three operations' applications and therapeutic effects. Methods The clinical data of 97 L/GCMN patients from June 1, 2015, to June 1, 2019, were collected and divided into three groups according to the operations used: serial excision group (SE group, n = 18), ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Each approach has its own challenges, especially in the management of large to giant CMN. Cheng and colleagues demonstrated that serial excision required more procedures but shorter operative times and hospital stays versus tissue expansion and skin grafting [64]. Grafting offered the least desirable cosmesis.…”
Section: Surgical Excisionmentioning
confidence: 99%
“…Each approach has its own challenges, especially in the management of large to giant CMN. Cheng and colleagues demonstrated that serial excision required more procedures but shorter operative times and hospital stays versus tissue expansion and skin grafting [64]. Grafting offered the least desirable cosmesis.…”
Section: Surgical Excisionmentioning
confidence: 99%
“…In summary, each of the three methods has respective benefits and drawbacks, thus the specific surgical strategy should be determined in light of the patient's particular circumstances. 71 For patients with GCMN, the complete excision of giant nevi is impractical in many cases due to the lack of skin for reconstruction.…”
Section: Surgerymentioning
confidence: 99%
“…In a retrospective study, the applicability and therapeutic outcomes were compared in patients with LCMN 71 . The authors found that the surgery length and hospital stay in the serial excision group were the shortest, while the times of operation were the highest.…”
Section: Treatments For Cmnmentioning
confidence: 99%
See 1 more Smart Citation